The Structural Model of Self-acceptance, Thematic Relationships and Hope for Employment through Mediating Sense of Agency and Its Effect on Life Quality of Blind and Low-vision Graduates - Fatemeh Asvadzadeh; Sahar Safarzadeh; Rezvan Homaei (Shahid Sadoughi University of Medical Sciences, 2023)
Background: The present study aims to use structural model in explaining the effect of unconditional self-acceptance, the quality of thematic relationships, and the hope for employment regarding the life quality of blind and visually impaired students based on the mediating role of the sense of agency. Methods: This study used descriptive research method of correlation type, which was carried out by structural equations. Moreover, this project was practical in terms of purpose. The statistical population of the current research included all the 12 to 35 blind and partially sighted people who were members of the Blind Association of Khuzestan province in 2022 with, university education (associate to doctorate). Targeted face sampling was used, and research tools included the following questionnaires: Life Quality of the Blind and Visually Impaired (2000), Unconditional Self-Acceptance (2001), the Quality of Subjective Relationships (1985), the Employment Hope (2007) and the Sense of Agency for People with Visual Impairments (2007). Data were analyzed using descriptive statistics and structural equation modeling (SEM). Results: The sum of squared multiple correlations (R2) for quality of life was equal to 0.58 (P = 0.001, β = 0.358). Accordingly, it can be said that the sense of agency mediates the effect of quality of the subject relationships regarding life quality of the blind graduates in a negative way, and the effect of hope for employment (β = 0.303, P = 0.001) and unconditional acceptance (β = 0.254, P = 0.001) on their life quality in a positive and meaningful way. Conclusion: Hope for employment and self-acceptance and the quality of local relationships as well as the sense of agency affect the life quality of blind and visually impaired people, and psychologists and people who are in contact with them.